The Information of Public Sciences: Definitions - Žiedonė Zaveckienė (Knygotyra)
Many different conceptions are noticed in defining information: mathematical, cybernetic, philosophical, philological, and bibliographical directions. There are quantitative and qualitative definitions, ranging from very complicated to more or less simple, and very close to the primary one.